EEG feature extraction using parametric and non-parametric models - Shiman, F.; Safavi, S.H.; Vaneghi, F.M.; Oladazimi, M.; Safari, M.J.; Ibrahim, F. (2012)
We have conducted extensive review on parametric and nonparametric methods for EEG feature extraction and application. We believe that this is the first attempt to compare all methods. Our findings indicate that parametric method does not provide good performance for EEG signal while non-parametric method lack of detail information on the EEG analysis. Â© 2012 IEEE.